Compositional functional regression and isotemporal substitution analysis: Methods and application in time-use epidemiology - Jašková, Paulína; Palarea-Albaladejo, Javier; Gába, Aleš; Dumuid, Dorothea; Pedišić, Željko; Pelclová, Jana; Hron, Karel (Statistical methods in medical research, 2023)
The distribution of time that people spend in physical activity of various intensities has important health implications. Physical activity (commonly categorised by the intensity into light, moderate and vigorous physical activity), sedentary behaviour and sleep, should not be analysed separately, because they are parts of a time-use composition with a natural constraint of 24 h/day. To find out how are relative reallocations of time between physical activity of various intensities associated with health, herewith we describe compositional scalar-on-function regression and a newly developed compositional functional isotemporal substitution analysis. Physical activity intensity data can be considered as probability density functions, which better reflects the continuous character of their measurement using accelerometers. These probability density functions are characterised by specific properties, such as scale invariance and relative scale, and they are geometrically represented using Bayes spaces with the Hilbert space structure. This makes possible to process them using standard methods of functional data analysis in the L2 space, via centred logratio (clr) transformation. The scalar-on-function regression with clr transformation of the explanatory probability density functions and compositional functional isotemporal substitution analysis were applied to a dataset from a cross-sectional study on adiposity conducted among school-aged children in the Czech Republic. Theoretical reallocations of time to physical activity of higher intensities were found to be associated with larger and more progressive expected decreases in adiposity. We obtained a detailed insight into the dose-response relationship between physical activity intensity and adiposity, which was enabled by using the compositional functional approach.
Keywords: Cross-Sectional Studies; adipozita; Obesity; physical activity; Bayes Theorem; sleep; Child; dítě; obezita; Exercise; Compositional scalar-on-function regression; isotemporal substitution; Time Factors; lidé; Humans; Adiposity; probability density functions; časové faktory; průřezové studie; Bayesova věta; sedentary behaviour; cvičení